2015
DOI: 10.1002/hep.27973
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of apical sodium‐dependent bile acid transporter changes bile composition and blocks progression of sclerosing cholangitis in multidrug resistance 2 knockout mice

Abstract: Deficiency for mdr2, a canalicular phospholipid floppase, leads to excretion of low phospholipid “toxic” bile causing progressive cholestasis. We hypothesize that pharmacological inhibition of the ileal apical sodium-dependent bile acid transporter (ASBT) blocks progression of sclerosing cholangitis in mdr2−/− mice. 30-day-old, female mdr2−/− mice were fed high-fat chow containing 0.006% SC-435, a minimally absorbed, potent inhibitor of ASBT, providing on average 11 mg/kg/day of compound. Bile acids (BA) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 37 publications
(87 reference statements)
5
103
0
Order By: Relevance
“…More recently, the effects of ASBTi in animal models of cholestasis have been reported. Miethke et al [21] treated mdr2 -/-mice (an established animal model for chronic cholestasis with some features of sclerosing cholangitis) with SC-435 for 14 days. They observed an eightfold increase in faecal BA excretion associated with 65, 98.9 and 98.8% decrease in hepatic, serum and biliary concentrations of BAs, respectively.…”
Section: Experimental Evidencementioning
confidence: 99%
“…More recently, the effects of ASBTi in animal models of cholestasis have been reported. Miethke et al [21] treated mdr2 -/-mice (an established animal model for chronic cholestasis with some features of sclerosing cholangitis) with SC-435 for 14 days. They observed an eightfold increase in faecal BA excretion associated with 65, 98.9 and 98.8% decrease in hepatic, serum and biliary concentrations of BAs, respectively.…”
Section: Experimental Evidencementioning
confidence: 99%
“…In Mdr2 (Abcb4) -/-mice interruption of bile acids enterohepatic circulation via potent ASBT inhibitors A4250 or SC-435 increased fecal bile acid lost and markedly reduced biliary concentrations of potentially toxic bile acids. In line with 'toxic bile' hypothesis, biliary bile acid depletion led to the amelioration of bile duct injury, inflammation and fibrosis in cholestasis [129,130] .…”
Section: Bile Acids Receptors and Other (Nuclear Hormone) Receptorsmentioning
confidence: 72%
“…The ASBT inhibitor A4250, previously used in a clinical phase I study [50], showed improvement of cholestatic liver injury in multi-drug resistance P-glycoprotein 2-deficient mice [51]. In a similar study, 2 weeks of treatment with SC-435, a different ASBT inhibiting small molecule, demonstrated reduced bile acid pool size and attenuation of cholestasis in the same mouse model [52]. At present, human studies are being performed, but the outcome of these promising studies is not published yet (https://clinicaltrials.gov/ct2/show/NCT02061540).…”
Section: Inhibition Of Bile Acid Uptake To Ameliorate Cholestatic LIVmentioning
confidence: 95%